Optimizing Public Asset Management through Digital Integration, Accountability, and Sustainable Local Government Policies - Setiawan, Ady; Arevin, Ayat Taufik; Syavardie, Yimmi (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
Public asset management is a critical component in enhancing the efficiency, transparency, and sustainability of local governance. However, many regions in Indonesia continue to face challenges such as data inaccuracy, underutilized assets, and weak oversight systems. This study aims to propose a strategic framework for optimizing public asset management by integrating digital technology, reinforcing governance accountability, and developing sustainable local policies. A qualitative method with a systematic literature review design was employed, analyzing recent academic literature, government reports, and policy documents published between 2019 and 2024. The findings reveal that digital integration through platforms such as Geographic Information Systems (GIS), cloud-based asset tracking, and AI-powered analytics significantly improves asset visibility, utilization efficiency, and monitoring. Furthermore, accountability measures—including public audits, transparent budgeting, and civic engagement—enhance trust and reduce risks of corruption. Additionally, sustainable local policies that incorporate ESG principles, circular economy models, and public-private partnerships contribute to long-term asset value and community welfare. The synergy between these three strategic pillars—digitalization, accountability, and sustainability—produces a responsive and adaptive asset management system. This research contributes to the development of a conceptual model linking digital transparency with policy effectiveness and operational efficiency. It is expected to serve as a practical guide for local governments in formulating integrated asset governance strategies that align with the evolving demands of public service delivery.